Tabletops - Horizontal Interactive Displays - M<U+00fc>ller-Tomfelde, Christian. (Human-Computer Interaction Series,, 2010)
Tabletops - Horizontal Interactive Displays - are compelling interfaces with unique characteristics. In everyday work, education and entertainment environments, tabletops can provide a stunning experience of intuitive interaction by direct touch and gestures ideal for small group collaboration. Recent developments of various technologies such as display and multi-touch technologies open up new possibilities to enrich interaction on horizontal interactive displays. Bringing together current research in the domain of tabletops, this book integrates and summarises findings from the most important international tabletop research teams in 18 chapters. It provides a state-of-the art overview and allows for the discussion of emerging and future directions in research and technology of tabletops. An introductory chapter, presenting a short history of tabletop research, technologies and products precedes the three major parts of the book, titled: "under", "on and above" and "around and beyond" tabletops. These parts are associated with different research disciplines such as Hardware/ Software and Computer Science, Human Computer Interaction (HCI) and Computer Supported Cooperative Work (CSCW). Fellow tabletop researchers, practitioners who consider deploying interactive tabletops in real-world projects and interested readers from other research disciplines will find the book an excellent reference source which also provides a useful introduction into tabletop research for the academic curriculum.